Water in Hinduism: Continuities and Disjunctures Between Scriptural Canons and Local Traditions in Nepal - Sharma, Sudhindra (Water Nepal, 2003)
Water is a multifaceted symbol in Hinduism. It is regarded as one of the pancha-tatva or five primeval elements of the universe. While the notions of water as primal matter, an instrument of purification and expiation, a unifying force, and a vivifying element can all be found in Hinduism, in most dharmashastras or Hindu religious texts, the symbolism of water as an instrument of purification and expiation is pre-eminent. The continuities between written Hindu traditions and local discourses in a Hindu community include such practices as snana (ritual bathing) and tirtha (pilgrimage), the notion of water as basi (stale) sazi (fresh) or raamro (good) and the association of ritual purity and pollution with water. The continuities between certain caste practices prevalent in the hill Hindu community, like not allowing Dalits (untouchables) access to water sources, and the caste and water pollution instructions of the written texts are, however, weak. Discontinuities also exist. The dispensing of snana in favour of ordinary bathing among the younger generation is one example. Another is the disjuncture between written Hinduism’s instructions about the profuse use of water and its actual sparse use in the local community. A disjunction is also apparent between the scriptural view of water and the view of modern legislation. While the dharmashastras associate water with cleanliness and ritual purity and leave the ownership of water undefined, Nepal’s modern laws views water as a resource and vests its ownership in the State. Giving the convenience and economic benefit of the general public as its rationale, the State has increasingly expanded its role in controlling and managing this national resource. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.215-247